What is the ideal time to provide corrective feedback? Replication of Li, Zhu & Ellis (2016) and Arroyo & Yilmaz (2018). (26th January 2020) - Li, Shaofeng
Abstract : This article calls for replication of two studies (Li, Zhu & Ellis 2016; Arroyo & Yilmaz 2018) that examine the timing of corrective feedback, which refers to whether errors should be corrected during a communicative task (immediate feedback) or after the task is completed (delayed feedback). The article starts with a rationale for replicating the two studies: they address a topic of significance to theorists, researchers, and practitioners; they are conducted with rigorous methods; they represent classroom and laboratory research respectively; they both show an advantage for immediate feedback. It proceeds to contextualize the subsequent discussion of replication strategies by (1) elaborating the theoretical claims and pedagogical positions on the influence of the timing of corrective feedback on learning outcomes and task performance, and (2) summarizing the findings of the research on the effectiveness of corrective feedback. After some background information is provided, a detailed discussion is given for each of the two studies, including a summary of the methods and findings, followed by recommendations about how to replicate.